Criminalizing Sexual Harassment Against Individuals Aged 16 and Above: Reasons and Recommendations for Vietnam - Nguyen Ngoc Toan; Cao Ngoc Anh Thi (PRAWO i WIĘŹ, 2026)
Sexual harassment is a serious violation of the victim’s honor and dignity, which contributes to social instability. As a Southeast Asian country deeply influenced by Confucianism with its patriarchal traditions, Vietnam has long faced the problem of sexual harassment, especially against women. In recent years, Vietnam has made progress in raising awareness and using the legal framework to combat this behavior. Currently, Vietnamese law provides for administrative and labor disciplinary sanctions against sexual harassment, and criminal prosecution is available if the victim is under 16 years old. However, a gap exists in the Vietnamese legal system as there is no provision for criminal liability for sexual harassment against victims aged 16 and above. This creates limitations in the protection of victims and reduces the deterrent effect of sanctions. Without clear criminal sanctions, victims tend to remain silent and are reluctant to report, knowing that the perpetrator will face only minor administrative penalties that are not commensurate with the harm suffered. This study, based on international and Vietnamese legal frameworks and an analysis of the current situation in Vietnam, aims to assess the necessity of establishing criminal liability for sexual harassment against victims aged 16 and above. The study also offers recommendations that Vietnam should consider when implementing this provision.